2014
DOI: 10.1089/ten.tea.2013.0642
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Tissue Engineering Application of Injectable Gelatin Hydrogel with In Situ Visible-Light-Activated Gelation Capability in Both Air and Aqueous Solution

Abstract: Chondroprogenitor cells encapsulated in a chondrogenically supportive, three-dimensional hydrogel scaffold represents a promising, regenerative approach to articular cartilage repair. In this study, we have developed an injectable, biodegradable methacrylated gelatin (mGL)-based hydrogel capable of rapid gelation via visible light (VL)-activated crosslinking in air or aqueous solution. The mild photocrosslinking conditions permitted the incorporation of cells during the gelation process. Encapsulated human-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 26 publications
6
128
0
Order By: Relevance
“…Expanding on these findings, this study explores the effect of urea-soluble extracts of the inner and outer meniscus ECM in promoting chondrogenic/fibrochondrogenic differentiation of MSCs seeded in a visible light (VL) photocrosslinked methacrylated gelatin (GelMA) hydrogel. GelMA hydrogels have been shown to support robust chondrogenesis of encapsulated MSCs [23] while the use of a VL-activated photoinitiator obviates concerns of UV light-induced mutagenesis or cytotoxicity [24]. We hypothesized that the ECM extracts would promote region-specific cell phenotypes, with the inner and outer ECM extracts respectively enhancing chondrogenic and fibrochondrogenic differentiation of MSCs seeded in GelMA hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Expanding on these findings, this study explores the effect of urea-soluble extracts of the inner and outer meniscus ECM in promoting chondrogenic/fibrochondrogenic differentiation of MSCs seeded in a visible light (VL) photocrosslinked methacrylated gelatin (GelMA) hydrogel. GelMA hydrogels have been shown to support robust chondrogenesis of encapsulated MSCs [23] while the use of a VL-activated photoinitiator obviates concerns of UV light-induced mutagenesis or cytotoxicity [24]. We hypothesized that the ECM extracts would promote region-specific cell phenotypes, with the inner and outer ECM extracts respectively enhancing chondrogenic and fibrochondrogenic differentiation of MSCs seeded in GelMA hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…To address such restriction on construct thickness, thermo-responsive or chemically initiated crosslinkers may be considered. The VL-based photocrosslinking technique employed in our study is biocompatible, as our previous study found less than 6% cell death in the encapsulated cell population [52]. By combining the two aforementioned characteristics, we have achieved a robust and instant integration of scaffold layers that is compatible with simultaneous, sufficient cell encapsulation.…”
Section: Discussionmentioning
confidence: 86%
“…Methacrylated gelatin (mGLT) was synthesized using an established protocol with slight modification [29, 34]. Gelatin (GLT, Sigma-Aldrich) was dissolved in deionized H2O at 37 °C (30%, w/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, use of lower wavelengths would likely cause increased damage to irradiated cells. Recently, visible-light photoinitiator such as lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) have been increasingly applied for photopolymerization of cell-laden hydrogels with very good cytocompatibility and short gelation times [421,422]. Since UV irradiation may lead to the formation of reactive oxygen species and subsequent cell damage [423], it is expected that the use of LAP and other visible-light photoinitiators in cartilage tissue engineering applications will further increase in future.…”
Section: Limitationsmentioning
confidence: 99%